2022
DOI: 10.1186/s12913-022-08010-5
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities of telehealth digital equity to manage HIV and comorbidities for older persons living with HIV in New York State

Abstract: Background Older persons living with HIV (PLWH) need routine healthcare to manage HIV and other comorbidities. This mixed methods study investigated digital equity, constituted as access, use and quality, of HIV and specialty telehealth services for PLWH > 50 years during the initial wave of the COVID-19 pandemic when services transitioned to remote care. Methods A survey of closed and open-ended questions was administered to 80 English (N = 63)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…For instance, one New York study found that PWH 50 years or older described telehealth as “too negative” for having fewer interpersonal components, particularly patient-provider relationship elements. Also, participants in the New York study with less formal education that utilized telehealth had poorer health outcomes than patients with high educational levels [ 45 ]. Similarly, in another study, racial minority telehealth users, particularly African Americans, had higher odds of unsuppressed viral loads than other racial or ethnic groups who utilized telehealth [ 13 ].…”
Section: Unresolved Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one New York study found that PWH 50 years or older described telehealth as “too negative” for having fewer interpersonal components, particularly patient-provider relationship elements. Also, participants in the New York study with less formal education that utilized telehealth had poorer health outcomes than patients with high educational levels [ 45 ]. Similarly, in another study, racial minority telehealth users, particularly African Americans, had higher odds of unsuppressed viral loads than other racial or ethnic groups who utilized telehealth [ 13 ].…”
Section: Unresolved Challengesmentioning
confidence: 99%
“…A persistent and significant concern regarding telehealth utilization among patients is the issue of data security [ 26 , 42 , 45 , 49 ]. Consistently reported in the literature, patients are concerned about the breach of data.…”
Section: Unresolved Challengesmentioning
confidence: 99%
“…When examining telephone visits, younger versus older and Black versus “Other” race PWH were more likely to have a no-show. In line with this, a qualitative study exploring experiences associated with telehealth use among older PWH (> 50 years) found older individuals to prefer telephone visits over video visits [ 20 ]. These results, which illustrate more sociodemographic differences in retention in care outcomes for in-person versus telehealth visits, suggest that telehealth visits may help ameliorate some of the structural barriers that contribute to health disparities.…”
Section: Discussionmentioning
confidence: 96%
“…Radhakrishnan et al ( 43 ) reported that for patients with heart failure on telehealth, comorbidity characteristics of renal failure, cancer, and depression comorbidities were significantly associated with withdrawal from telehealth services. However, a more recent study showed that for older persons living with HIV, the number of comorbidities was positively related to telehealth use via telehealth apps such as the MyChart App ( 44 ). Because of risk factors for severe COVID-19, the role of telehealth use will become more and more critical for the early identification of patients who need their care, care coordination, and the assessment of daily facility needs.…”
Section: Discussionmentioning
confidence: 99%